An ASSESSMENT OF E-TAX ADMINISTRATION ON TAX REVENUE IN ONDO STATE, NIGERIA - Oladele Patrick Olajide; Aribaba Foluso Olugbenga; Oladele Rotimi Adekokun; Ahmodu Ahmodu; Olamide Lateef (Journal of Business Studies and Management Review, 2019)
The study assessed the impact of e-tax administration on tax revenue in Ondo state internal revenue, Nigeria. The study employed survey research design using primary data sourced from the distribution of a well-structured questionnaire to the staff of the Ondo State Board of Internal Revenue (OSBIR). Data collected were analyzed using descriptive and inferential statistics; through frequency counts, mean scores; and Z-test to test the hypotheses formulated. The study revealed that electronic taxation has significant influence on tax evasion as demonstrated by the calculated Z-test score greater than the Z-table score of (1.96 < 6.44); similarly, it was also shown that electronic-taxation can prevent corrupt practices among some tax administrators as revealed by the Z-table score of (1.96 < 3.08). The study concluded that e-taxation can reduce tax evasion in Nigeria as well as truncate corrupt practices among tax officials in Nigeria. It was recommended that OSBIR embrace e-taxation with urgent deployment of robust Information Technology; and encourage regular training of staff and taxpayers sensitization to facilitate smooth running. This will engender a high level of compliance among taxpayers. Also, e-tax ought to be employed in order to ease the related glitches that swindling stakeholders’ interest.